Imobilização de α-galactosidase de Aspergillus niger em suporte de quitosana por ligação cruzada - Oliveira, Rodrigo Hipólito Azevedo de (2012)
The general aim of this work was to study the process of α-galactosidase immobilization in support of chitosan by cross-linking using glutaraldehyde. The influence of glutaraldeyde concentration as crosslinker agent and activity time reaction on a immobilized byocatalyst were either studied using a factorial design. Further, a study on the influence of the enzyme concentration, temperature and pH on the immobilization process was done using a central composite planning. Both the factorial design and central composite planning were used to indicate the maximum activity after enzymatic hydrolysis, employing raffinose as substrate. The results show that the glutaraldehyde concentration and the immobilization time were 5% (v/v) and 24 hours, respectively. The central composite planning results indicated that the catalytic activity\'s retention in the immobilization process was utmost at a enzyme concentration range of 12 to 20 g/L, pH among 6.5 to 8, and temperatures amid 22 to 340C. After, the stability study of α-galactosidase immobilized on chitosan with respect to pH and temperature were either developed. In these scenarios the pH range was of 3.0 to 9.0 for both immobilized enzyme particles with glutaraldehyde (5% v/v) as for those immobilized without glutaraldehyde (0% v/v); and testing for thermal stability occurred at temperatures between 50 and 60ºC for enzymes immobilized with glutaraldehyde. The outcomes indicated that the immobilized enzymes with 5% glutaraldehyde were stable throughout the pH range studied, since the immobilized enzymes without glutaraldehyde remained stable in the range between 5.0 and 9.0. Regarding the heat treatment during the time periods studied, it was found that the enzyme activity decreased with increasing temperature and time of exposure. Results related to the stock time resistance of immobilized α-galactosidase on chitosan both with and without glutaraldehyde showed that, after 50 days, for the process with crosslinker there was residual activity of 73.77% and for the case lacking glutaraldehyde the residual acivity was 14,38%. At the trial resistance concerning the number of repetitions, the results indicate that for the immobilized enzyme with glutaraldehyde the residual activity was 82,56% after 20 uses.